The Politics of the Hajj from a Comparative Perspective
XIX, 251 p. 16 illus., 13 illus. in color.
Keywords: "This volume offers an important transnational and historical examination of the contemporary politics of the Hajj. It adds a great deal to the literature that has been waiting for new and fresh insights into the management of an institution that has acquired overtime increased socioeconomic and political significance." -- Aboulaye Sounaye, Head of Research Unit Contested Religion and Intellectual Culture, at the Leibniz-Zentrum Moderner Orient, Germany “One of the book’s strengths is its comparative aspect across different countries and periods. It highlights the main issues behind the politics of organizing the Hajj, i.e. security, legitimation and clientelism, as well as the construction of citizenship. This volume constitutes an essential reading not only for scholars and students but also for policymakers.” --Aminah Mohammad-Arif, Research Director at the Centre d'études sud-asiatiques et himalayennes (EHESS/CNRS), France “The present volume addresses the questions of control, and, thus, of politics surrounding the Hajj from multidisciplinary perspectives. Due to this multi-vocal approach the present volume is a welcome and highly overdue contribution to our knowledge of the Hajj.” --Roman Loimeier, Professor at the Institute of Social and Cultural Anthropology, Göttingen University, Germany This book analyzes the contemporary politics of the Hajj in countries of Africa (Ghana, Morocco, Nigeria), the Near East (Palestine, Saudi Arabia), and Southeast Asia (Indonesia, Malaysia). It studies two aspects of the Hajj organization: first, the power relations states develop with pilgrims, religious leaders, and entrepreneurs, and how these relations impact their domestic legitimacy, internal security, and geopolitical positioning. Second, how pilgrims make sense of, and navigate, the bureaucratic apparatus they encounter, both at home and in Saudi Arabia. Muriel Gomez-Perez is Full Professor in the Interdisciplinary Research Center on Africa and the Middle East (CIRAM), Department of Historical Sciences, Université Laval, Canada. Cédric Jourde is Associate Professor in Political Studies at the University of Ottawa, Canada. Marie Brossier is Full Professor in the Interdisciplinary Research Center on Africa and the Middle East (CIRAM), Department of Political Science, Université Laval, Canada.